Cs2AgxNa1-xBiyIn1-yCl6 perovskites approaching photoluminescence quantum yields of 100% - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Kupfer, Christian; Osvet, Andres; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Hauch, Jens; Brabec, Christoph J. (Materials Advances, 2022)
A new single-step and green approach for the synthesis of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites in ambient conditions is introduced. The CANBIC powders emit broadband self-trapped excitonic photoluminescence (PL) with a champion PL quantum yield (QY) of 98 +/- 2% and a PL lifetime of ca. 2 mu s observed for x = 0.40 and y = 0.01-0.02. The study focuses on the dependence of structural, spectral, and photophysical properties of CANBICs on Bi content. CANBICs are solid solutions with isomorphous In-to-Bi substitution with the bandgap and valence band edge energy decreasing gradually with increasing y. The PL QY and the rate constant of the radiative recombination showed volcano-shaped dependences on the Bi content, while the rate of the non-radiative recombination revealed a drastic growth by three orders of magnitude as the Bi fraction y was elevated from 0.01 to 1.0 indicating that BiCl6 units are responsible for non-radiative recombination.
CRIS-Team WoS Importer:2022-09-09